Predictors of Sexual Addiction among Medical Undergraduates during the COVID-19 Pandemic: A Cross-sectional Survey - Pranjal Sharma; S Sourabh; Vallabh Shet; Shankar Kumar; Sharanya Kaushik; Mohammed Shoyaib Khazi; Yamasandhi Mallegowda Jeevan (Indian Journal of Private Psychiatry)
Background: Medical students are at higher risk of adverse mental health outcomes, more so in the context of the COVID-19 pandemic. As a result of maladaptive coping mechanisms to stress, they are more likely to develop substance and behavioral addictions. This study was carried out to identify associations between sexual addiction and several psychological determinants, considering the paucity of literature regarding sexual addiction in this population. Materials and methods: Using the snowball sampling technique, an online survey was carried out among undergraduate students at a government medical college. Assessment tools included Young's Internet Addiction Test, Sexual Addiction Screening Test, WHO ASSIST V 3.0, MSPSS, DASS-21, PANAS-GEN, McMaster Family Assessment Device, UCLA Loneliness Scale, Fear of Coronavirus 19 scale. The objectives were to determine the prevalence of sexual addiction in this demographic and to assess its psychological factors. SPSS v27.0 Grad Pack was used to analyze the data. Results: Out of the 106 participants, 21 (19.8%) screened positive for sexual addiction. Sexual addiction was identified to have a significant positive association with internet addiction (p = 0.02), alcohol use (p = 0.00), depression (p = 0.03) and stress (p = 0.03), and a significant negative association with perceived social support from friends (p = 0.02) and family (p = 0.05). Stepwise multiple linear regression found alcohol use, perceived social support of friends and time management and performance domain of internet addiction test (IAT) to predict sexual addiction. Conclusion: The results point to a significant co-occurrence of problematic patterns of substance use and behaviors suggestive of addictions. This highlights that common vulnerabilities may underlie addictions. Knowledge of sexual addiction risk factors will have immense clinical utility be it to identify vulnerable individuals or to plan interventions that target these risk factors while treating sexual addictions.